Urdu ka guldasta revised edition Gul e lala (for class 5) - Fouzia ahsan farooqui (Oxford University Press; Pakistan, 2022)
Gul-e-Lala Class 5 is an educational resource that provides a variety of lessons, stories, and exercises to support the learning and development of fifth-grade students.